Attenuated Listeria monocytogenes as a Vaccine Vector for the Delivery of OMPW, the Outer Membrane Protein of Aeromonas hydrophila - Zeng, Haijuan; Xie, Manman; Ding, Chengchao; Ma, Junfei; Xu, Dongpo; Wang, Xiang; Qiu, Jingxuan; Liu, Qing (Frontiers in Microbiology, 2020)
Listeria monocytogenes (LM) is a gram-positive facultative intracellular pathogen that could stimulate host to produce inflammatory response, cell-mediated immunity and humoral immunity. In this study, an attenuated live vector vaccine for Aeromonas hydrophila (AH) named EGDeABdd-dat-ompW was successfully constructed using an attenuated vector named EGDeABdd which dal, dat, actA and inlB genes were deleted from wild type LM-EGDe. To construct EGDeABdd-dat-ompW, a recombinant plasmid pERL3-dat-ompW obtained by inserting dat gene from EGDe and outer membrane protein gene ompW from AH into pERL3 plasmid was transformed into EGDeABdd cell. The safety and immunogenicity of EGDeABdd-dat-ompW as attenuated vector vaccine for delivery OMPW was assessed through analyzing invasion to Caco-2 cells and mice, cytokines production of macrophagocyte and mice splenocytes, and T cells proliferation of mice splenocytes. Serum titers against AH and immunoprotective effect of vaccine to mice were also measured after intravenous injection with vaccine for 4 times. The results showed that the live vector vaccine EGDeABdd-dat-ompW for AH exhibited highly attenuation in invading Caco-2 cells and mice compared to EGDe. RT-PCR showed that cytokines, e.g., TNF-α, IL-6, IL-1β from macrophages, and IL-6, IFN-γ from mice splenocytes had significantly increased after immunization by EGDeABdd-dat-ompW. Meanwhile, the vaccine could induce producing CD3+CD4+ and CD3+CD8+ T cells proliferation of mice and generate effective immune protection against lethal challenge by 20×LD50 AH. All these results indicated that the attenuated EGDeABdd-dat could be used as a live vector to delivery exogenous gene, not only possessing safety, but also providing high immunogenicity. The successful application in AH vaccine further showed that it could be used in other fields such as vaccine in cancer or infectious disease.